International competitiveness, investment and finance : a case study of India - Ganesh-Kumar, A.; Sen, Kunal; Vaidya, Rajendra R. (London ; New York : Routledge, 2003)
Using India as a case study, this well-written, concise book covers everything one needs to understand how a country becomes internationally competitive, and makes a compelling case for complimentary financial sector reforms.
Includes bibliographical references (p. [151]-156) and index.
oif 29/07/16 ; rpm 30/08/16
Loans
Keywords: Competition, International; Investments, Foreign; Corporations; Balance of payments; International economic relations; Commercial policy; India